An investigation into surface effects in thin film plastic scintillators - Wentzel, John P (Department of Physics, 2016)
An investigation into the luminescent response of thin film plastic scintillators as a function of their method of preparation is made. Investigations are carried out on NE102A and NE118 using four different methods of preparation. It is found that the Birks model for luminescence as a function of film thickness successfully explains the response in three of the four methods of preparation, but fails to explain the response of thin films prepared on a glass surface. These films show an unexpected non-linearity in their behaviour. It is proposed that the behaviour in these films can be explained in terms of the existence of surface regions in these films. A model based on the existence of these surface regions is prepared. It is further proposed that, in general, the luminescent response of thin films of plastic scintillator is dependent on their method of preparation.